Impacts caused by the use of screens during the COVID-19 pandemic in children and adolescents: an integrative review - Maria Alice Aparecida Resende; Mariana Luiza da Fonseca; Jéssica Tertuliano de Freitas; Elaine Cristina Rodrigues Gesteira; Lisabelle Mariano Rossato (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To identify the scientific evidence on the impacts caused by the use of screens during the COVID-19 pandemic in children and adolescents, raising reflections for future interventions with this public. Data source: This is an integrative literature review, conducted in the databases Medical Literature Analysis and Retrieval System Online (MEDLINE), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Cumulative Index to Nursing and Allied Health Literature (CINAHL), United States National Library of Medicine (PubMed), Scopus, Web of Science, and Embase, published from March 2020 to January 2022, in Portuguese, English and Spanish. Data synthesis: The search strategies allowed retrieving 418 articles, of which 218 were duplicates. The analysis of titles and abstracts resulted in the maintenance of 62 studies. Of these, 31 were excluded from the reading of the full text, since they did not clearly present the phenomenon investigated. Thirty-one were eligible, resulting in five categories: eye consequences; increased sedentary behavior and weight; change in eating habits; implications for sleep quality and impacts on mental health. Conclusions: The excessive use of screens during the pandemic led to numerous consequences for children and adolescents, with a higher incidence of visual damage, sedentary lifestyle, inadequate eating habit and increased weight gain, in addition to impaired sleep quality and mental health. This study provides subsidy for health professionals to carry out continuing education focused on this theme, and elaborate effective interventions for this public in this transition to the post-pandemic period.